Appropriateness and safety of using the intranasal route for sedation during pediatric computed tomography: A randomized controlled trial at Korle-Bu teaching hospital - Beauty Naa Yarley Annan; Ebenezer Owusu Darkwa; Audrey Anno; Naa Matekour Vanderpuye; Lorraine Baffour-Awuah; Grace-Imelda Obeng Adjei; Owusu-Sekyere Danso; Raymond Essuman; George Aryee; Robert Djagbletey (Journal of International Medical Research, 2025)
Objective This study aimed to determine the effectiveness and safety of using intranasal ketamine, midazolam, or their combination for sedation during pediatric computed tomography. Method In this randomized, double-blind study, 60 children aged ≤2.5 years who were scheduled to undergo computed tomography were allocated into the following three groups: Group K (ketamine 10 mg/kg), Group M (midazolam 0.2 mg/kg), and Group C (ketamine 7.5 mg/kg + midazolam 0.1 mg/kg). In all cases, the drugs were administered intranasally. Sedation parameters were assessed. Result Of the 60 randomized participants, 10 were excluded due to failed sedation. Data from 16 (Group M), 14 (Group K), and 20 (Group C) participants were analyzed. The mean sedation scores were similar: Groups K (2.86 ± 0.38), M (2.63 ± 0.74), and C (2.70 ± 0.68) (p = 0.579). Time to adequate sedation was shortest in Group C (22 ± 9 min; p = 0.022). Recovery was fastest in Group M (63 ± 25 min; p = 0.007). Discharge times differed significantly (p = 0.036) among the groups, with Group M exhibiting a discharge time of 92 ± 29 min. Group C had superior parental separation scores compared with the other groups (p = 0.035). Conclusion Intranasal administration of ketamine, midazolam, or their combination is safe and effective for inducing sedation during computed tomography in pediatric patients with minimal side effects.